Internal Control And Cyber Risk Mitigation In The Regional Government Information System (SIPD): Evidence From Tabanan Regency Government, Indonesia - Chinta Nadia; Sherly Alika Zefanya; Rimi Gusliana Mais (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2026)
The increasing adoption of digital technologies in public sector organizations has transformed regional financial management practices while simultaneously exposing local governments to growing cybersecurity risks. In Indonesia, the Regional Government Information System (Sistem Informasi Pemerintahan Daerah—SIPD) has become a strategic platform for integrating planning, budgeting, administration, and financial reporting processes. Despite the widespread implementation of SIPD, previous studies have primarily focused on administrative effectiveness and financial reporting quality, with limited attention given to the role of internal control in mitigating cyber risks within local government information systems. This study aims to analyze the role of internal control as a cyber risk mitigation mechanism in the implementation of SIPD within the Tabanan Regency Government, Indonesia. A qualitative descriptive approach was employed using secondary data obtained from official government documents, public reports, regulatory documents, and relevant academic literature. Data were analyzed through data reduction, data presentation, and conclusion drawing to identify the relationship between internal control practices and cyber risk management in SIPD implementation. The findings indicate that SIPD has strengthened the integration of regional financial management processes and supported the advancement of digital governance in Tabanan Regency. Furthermore, internal control contributes significantly to cyber risk mitigation by enhancing user access monitoring, ensuring data accuracy, strengthening system supervision, and protecting digital financial information from potential cybersecurity threats. Effective internal control mechanisms help maintain accountability, system reliability, and information security in digital-based financial administration. This study contributes to the literature by extending the discussion of SIPD beyond financial reporting effectiveness toward cyber governance and information security perspectives. Practically, the findings provide insights for local governments seeking to strengthen cybersecurity readiness and internal control frameworks to support sustainable digital governance and secure public financial management.